Neighborhood Context, Street Efficacy, and Fear of Violent Victimization - Yuan, Yue (Youth violence and juvenile justice, 2017)
Drawing on Bandura’s self-efficacy theory, the current study investigates the relationship between individuals’ perceived self-efficacy of avoiding unsafe situations and fear of violence in a neighborhood context. Specifically, it is hypothesized that adolescents who report higher levels of street efficacy are less likely to exhibit fear of violence than adolescents who report lower levels of street efficacy. Using panel data from the Project on Human Development in Chicago Neighborhoods, the authors estimate a series of multilevel ordinal logistic regression models to explain the relationship between street efficacy and fear of violence controlling for both individual-level and neighborhood-level covariates. The results confirm the hypothesis that adolescents’ prior street efficacy is negatively associated with subsequent fear of violence. The current study suggests that a social cognitive perspective should be incorporated into the fear of crime literature. Policy implications of the findings are discussed, along with suggestions for future research.